DOES COMBAT DEPLOYMENT EXPERIENCE AFFECT THE COMMANDER’S DECISION-MAKING PROCESS? (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents the results of a study conducted in 2022. An attempt is made to determine whether commanders' perceptions of the importance of the mission's variables change as a result of gaining combat deployment experience. A critical assessment of the mission variables is the focus of the research, which examines the importance of these variables according to the tactical commanders who plan the operations. The methods used are expert judgment elicitation and statistical analysis. The results show that combat deployment experience appears to have only a minor impact on commanders' decision-making process. The ranking list developed using the input of the experts' group, which includes officers with combat experience, may serve as a basis for improving existing models for assessing the mission variables. In order to expand the collection of research data and increase the significance of the findings, the methodology used in the study could be applied to other expert groups outside the Bulgarian armed forces.